HIV-2: the forgotten AIDS virus. - de Silva, T; Cotten, M; Rowland-Jones, S (2008)
HIV type 2 (HIV-2), a closely related retrovirus discovered a few years after HIV type 1, causes AIDS in only a minority of infected individuals. Determining why HIV-2 causes asymptomatic infection in most patients could further our understanding of HIV immunopathogenesis. Studies to date have suggested that both enhanced immune responses and lower viral replication could play a role. We summarize the important findings to date and highlight areas that warrant further exploration.